Herbicide-resistant crops : A weed scientist’s perspective - Dyer, W.E. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
Herbicide-resistant crops offer a potentially valuable alternative strategy for weed management. If used appropriately, they may promote the use of agrichemicals more environmentally benign than the herbicides they replace, and provide producers with additional tools for controlling weeds. However, the controversy surrounding the development and use of these cultivars may limit and eventually prevent their widespread adoption. Concerns include: overuse of herbicides, escape of herbicide resistance genes from resistant cultivars into weedy relatives, genetic modifications for resistance conferring weediness to the cultivar (i.e. volunteer plants insubsequent crops), potential pleiotropic effects of genetic modifications for resistance, and selection of new herbicide-resistant weeds in the new herbicide regime. Of these concerns, the potential for selecting new resistant weeds may have the highest likelihood of affecting the long-term success of herbicide-resistant crops.